Microbial Growth on Dichlorobiphenyls Chlorinated on Both Rings as a Sole Carbon and Energy Source - Kim, Sanggoo (American Society for Microbiology, 2001)
We have isolated bacterial strains capable of aerobic growth on ortho-substituted dichlorobiphenyls as sole carbon and energy sources. During growth on 2,2′-dichlorobiphenyl and 2,4′-dichlorobiphenyl strain SK-4 produced stoichiometric amounts of 2-chlorobenzoate and 4-chlorobenzoate, respectively. Chlorobenzoates were not produced when strain SK-3 was grown on 2,4′-dichlorobiphenyl.